The modified cross-suture technique for unilateral pulled-out anchor during all-inside meniscal repair - Jianlong Ni; Zhibin Shi; Lihong Fan; Ning Guo; Haoyu Wang; Xiaoqian Dang; Dichen Li (BMC Musculoskeletal Disorders, 2020)
Abstract Background Meniscal repair has received increasing attention, but for inexperienced doctors, unilateral suture anchor pulling out may occur during all-inside meniscal repair, and the treatment outcome may be affected. When the errors happened intraoperatively, how to minimize the loss under guaranteeing of treatment effectiveness is a topic worth studying. Purpose To explore the practicability and effectiveness of the modified cross-suture method for arthroscopic remediation of unilateral suture anchor pulling out of an all-inside meniscal repair system. Methods From May 2014 to May 2017, 28 patients diagnosed with injuries of the meniscus and anterior cruciate ligaments (ACL) from the First Department of Orthopaedics of the Second Affiliated Hospital of Xi’an Jiaotong University were enrolled in the study as the observation group, including 18 males and 10 females with an average age of 25.5 ± 2.3 years (range 18–42 years). All patients underwent ACL reconstruction concurrently. All meniscus injuries were repaired with an all-inside meniscal repair technique, and 1–3 needles of unilateral suture anchor pulling out occurred intraoperatively. The modified cross-suture method was used to remedy the error of anchor pulling out and to eventually complete an effective repair. Another 30 patients who underwent ACL reconstruction and all-inside meniscal concurrently without unilateral suture anchor pulling out, including 20 males and 10 females with an average age of 26.3 ± 1.9 years (range 19–45 years), were enrolled as the control group. During postoperative follow-up, range of motion, Lachman test and pivot shift test were performed during the physical examination. The clinical healing of the meniscus was evaluated according to the Barrett standard. The meniscus healing status was also confirmed with magnetic resonance imaging (MRI). The function of the knee joint was evaluated according to the IKDC, Lysholm and Tegner scores. Results Twenty-five patients in the observation group and 28 patients in the control group completed the follow-up, with an average follow-up of 18.4 ± 5.2 months. All operations were performed by the same surgeon. At the follow-up 1 year after the operation, the average knee ROM of the two groups was 125.2 ± 4.3 degrees and 124.7 ± 3.8 degrees, the clinical healing rate of the meniscus of the two groups was 92.0% (23/25) and 92.9% (26/28), the MRI healing rate of the menniscus of the two groups was 72.0% (18/25) and 71.4% (20/28), and the IKDC, Lysholm and Tegner scores of the two groups were 90.52 ± 2.8, 89.17 ± 3.1, and 6.81 ± 1.7 and 91.42 ± 1.9, 90.32 ± 3.4, and 7.02 ± 1.4, respectively. The differences were not statistically significant (P > 0.05). Conclusions The modified cross-suture method is practicable and effective for arthroscopic remediation of unilateral suture anchor pulling out in an all-inside meniscal repair system.